A facile preparation of robust superhydrophilic and underwater superoleophobic copper foam for high efficiency and repeatable oil–water separation. (3rd August 2021) - He, Jinmei; Wang, Rong; Pang, Yajie; Luo, Zhanxia; He, Dan; Sun, Wenchao; Shi, Fan; Peng, Lei; Qu, Mengnan
Abstract : Design of robust separation materials with superwettability for efficient oil–water separation is of great significance because of the serious problem of oil leakage. Herein, we have fabricated a superwetting material based on copper foam via chemical oxidation and hydrothermal method for oil–water separation. These modified copper foam with rough structure exhibit excellent superhydrophilicity and underwater superoleophobicity. Thus, it shows high oil–water separation efficiency (99%), excellent circulation and high‐flux (24, 129 Lm −2  h −1 ). Meanwhile, the modified copper foam exhibits favorable durability and stability under extreme environment conditions, such as immersion tests in salt, different pH conditions, high temperature and mechanical abrasion tests. Therefore, the modified copper foam has the advantages of high separation efficiency and remarkable stability, and is promising material, which can be used for the treatment of industrial oily wastewater.